Penerapan Model Pembelajaran Project Based Learning dengan Pendekatan STEM pada Materi Hukum-Hukum Termodinamika - Faisal; Makahinda, Tineke; Silangen, Patricia (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
This research was conducted to determine the application of a project-based learning model with a STEM approach to the material of thermodynamic laws to student learning outcomes. The method used in this study was pre-experiment with a one group pretest-posttest design. The study sample was 28 learners. Data analysis in this study used the SPSS 25 application. From the results of data analysis, the average pretest value was obtained 49.82 and posttest 80.54. From hypothesis testing using the t-test paired sample test obtained sig values. (2-tailed) is by 0.000 0.05. then the data shows that there is an increase in student learning outcomes using a project-based learning model with a STEM approach. thus, it can be concluded that the average score of physics learning outcomes of students given treatment using the application of a project-based learning model with a STEM approach is higher than the average score of physics learning outcomes before being given treatment.